Statin therapy compliance - N. Sh. Zagidullin; Sh. Z. Zagidullin (Кардиоваскулярная терапия и профилактика, 2008)
Recently, high effectiveness of long-term statin therapy has been demonstrated not only for hyperlipidemias, but also for various forms of coronary heart disease and high cardiovascular risk. Low therapy compliance restricts statins’ effectiveness substantially. Awareness of the factors determining low compliance facilitates prediction of patients’ attitude towards treatment, as well as planning of therapy monitoring and patient education. Choosing an effective statin, e.g., atorvastatin, gives an opportunity to achieve target lipid levels faster and provides adequate treatment compliance.